Образ В. Г. Короленко в творчестве удмуртских художников - Витрук Николай Васильевич (Удмуртия, 2003)
Экземпляры: аб. ЦБ (20210325) / Инвентарный номер: 10772 / Цена: / Сис.шифр: 85.1(2Рос.Удм) / Авт.знак: В 54 / ГРНТИ: 18.31.31 / ББК: 85.1(2Рос.Удм)